Study on the evolution mechanism of adiabatic shear bands during the deformation of medium carbon bainitic steel acted upon by high strain rates - Songbo Zhou; Feng Hu; Rui Ke; Hua Zheng; Yingying Wang; Houkui Xiang; Kaiming Wu (Journal of Materials Research and Technology)
The microstructure evolution and formation mechanism of adiabatic shear bands of bainitic steel during high strain rate deformation are methodically examined via a split Hopkinson pressure bar. The results show that the stress-strain relationship of the steel shows obvious strain rate dependence, i.e. with the increase of strain rate, the work hardening rate shows a trend of 8000 s−1 > 2000 s−1 > 500 s−1. The strain rate strengthening is mainly attributed to the slight refinement of grains, the fragmentation of some bainite laths and the proliferation of dislocations. With the strain rate increases, the crystal orientation gradually converges to (001) and (111). Very fine equiaxed grains appear in the ASB formed at 8000 s−1, which is attributed to local adiabatic heating and related thermo-mechanical instability. At a strain rate below 8000 s−1, the experimental steel undergoes uniform deformation, dislocation distribution, dislocation entanglement, and the formation of substructures including dislocation cell structures and sub-grains. Under the action of high-strain rate, the overlapping regions of activated dislocation sources and stress concentration regions arrive at the potential location of ASB nucleation. The research results lay a foundation for further optimizing and expansion of the application range of bainitic steel.